Physical Properties Comparison of rGO-like phase prepared from Coconut Shell and the Commercial Product - Retno Asih; Maya Mahirotul Septya; Erik Bhekti Yutomo; Fahmi Astuti; Malik Anjelh Baqiya; Darminto Darminto (Jurnal Fisika dan Aplikasinya, 2020)
Physical properties of reduced graphene oxide (rGO) prepared from two different raw materials, namely coconut shell (rGO-s) and graphite mineral (rGO-c, produced by Graphenea Inc.), have been investigated. While both samples have the same density of about 1.9 g/cm3, rGO-c has more porous of about 1.3 cc/g with diameter of 10.8 nm compared to rGO-s which has 0.2 cc/g porous with diameter of 2.4 nm. Specific surface area in rGO-c was also obtained much larger than that of rGO-s. rGO-c and rGO-s have specific surface area of ~298 m2/g and ~475 m2/g, respectively. Examinations on particle size and surface morphology show that rGO-c has homogenous particles which consist of transparent thin sheets, while rGO-s has rather heterogenous particles that look like dens stacked sheets. The presence of C and O was confirmed at the observed morphology. The difference in physical features were then found to influence the obtained electrical conductivity of the samples. rGO-c has higher conductivity than rGO-s. Estimation on gap energy (Eg) indicates that rGO-c and rGO-s have Eg in the range of semiconducting materials. The study provides a better understanding on physical properties of coconut shell-derived rGO to further revise synthesis method to improve quality of the obtained rGO.